Implementation of geriatric assessment and long-term care insurance system by medical professionals in cancer treatment: a nationwide survey in Japan. (23rd February 2022) - Yoshida, Yoichiro; Tamura, Kazuo; ,
Abstract: Background: A questionnaire survey was conducted to assess the implementation status of geriatric assessment in cancer treatment and the potential for collaboration between medical care and the long-term care insurance system. Methods: Questionnaires were sent to 795 facilities in Japan. The questions were instructed to be answered via an online survey (SurveyMonkey®), which began in September 2020 and closed on 31 October 2020. The questionnaire consisted of 8 questions on the status of geriatric assessment implementation and 15 questions on the long-term care insurance system. Results: In total, 631 departments in 340 (42.8%) of 795 hospitals and clinics provided responses. Approximately 81.5% of the departments did not perform geriatric assessment. The common reasons were lack of knowledge about geriatric assessment (54.0%) and lack of personnel (35.5%). Even if geriatric assessment was conducted, 63.6% of departments did not utilize geriatric assessment results in clinical practice. Approximately 61.7% of respondents were familiar with the long-term care insurance system and 62.9% with the certification process. Moreover, 28% of respondents used certification examination results in treatment planning. Conclusions: Geriatric assessment is less recognized than the long-term care insurance system, and its results are rarely used in clinical practice. However, 28% of certification examination results are utilized in treatment decision-making. Notably, this survey first showed the incorporation of the long-term care insurance system into the medical care of vulnerable elderly patients with cancer. Abstract : Geriatric assessment is less recognized than the long-term care insurance system, and its results are rarely used in oncological clinical practice.